2013
DOI: 10.1186/ar4395
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pain in fibromyalgia: insights into the symptom of fatigue

Abstract: Fatigue is a disabling, multifaceted symptom that is highly prevalent and stubbornly persistent. Although fatigue is a frequent complaint among patients with fibromyalgia, it has not received the same attention as pain. Reasons for this include lack of standardized nomenclature to communicate about fatigue, lack of evidence-based guidelines for fatigue assessment, and a deficiency in effective treatment strategies. Fatigue does not occur in isolation; rather, it is present concurrently in varying severity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 126 publications
4
79
2
4
Order By: Relevance
“…It bears mention that several other factors may play a role in explaining the relationship between pain intensity and physical functioning; previous research in other chronic pain populations has indicated that catastrophizing, fear of reinjury, and pain-related anxiety may impact this relationship as well (Denison, Asenlof, & Lindberg, 2004;Peters et al, 2004;Scott, Kroenke, Wu & Yu, 2016); and there is evidence that these factors contribute to the experience of depression as well (Sturgeon & Zautra, 2013). Another plausible relationship worth exploring is the role of fatigue/decreased energy; fatigue is a hallmark symptom of fibromyalgia, with some estimates suggesting prevalence rates as high as 76% in FM patients (Vincent, Benzo, Whipple, McAllister, Erwin, & Saligan, 2013). It stands to reason that fatigue may also play a role in the relationship between depression/negative affect and physical functioning/disability as it is correlated with both (Vincent et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It bears mention that several other factors may play a role in explaining the relationship between pain intensity and physical functioning; previous research in other chronic pain populations has indicated that catastrophizing, fear of reinjury, and pain-related anxiety may impact this relationship as well (Denison, Asenlof, & Lindberg, 2004;Peters et al, 2004;Scott, Kroenke, Wu & Yu, 2016); and there is evidence that these factors contribute to the experience of depression as well (Sturgeon & Zautra, 2013). Another plausible relationship worth exploring is the role of fatigue/decreased energy; fatigue is a hallmark symptom of fibromyalgia, with some estimates suggesting prevalence rates as high as 76% in FM patients (Vincent, Benzo, Whipple, McAllister, Erwin, & Saligan, 2013). It stands to reason that fatigue may also play a role in the relationship between depression/negative affect and physical functioning/disability as it is correlated with both (Vincent et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…Another plausible relationship worth exploring is the role of fatigue/decreased energy; fatigue is a hallmark symptom of fibromyalgia, with some estimates suggesting prevalence rates as high as 76% in FM patients (Vincent, Benzo, Whipple, McAllister, Erwin, & Saligan, 2013). It stands to reason that fatigue may also play a role in the relationship between depression/negative affect and physical functioning/disability as it is correlated with both (Vincent et al, 2013). Although we were unable to examine these factors in the present study, future research should attempt to further illustrate the complex relationships between psychological constructs, pain, fatigue, and functioning with FM patients; this work may involve looking for subgroups within the populations that exhibit various patterns of these other factors; this work would be especially important given the only partial mediation of our depression mediator.…”
Section: Limitationsmentioning
confidence: 99%
“…Evidence from clinical trials with TNF-α inhibitors suggests that improvement in disease activity is associated with improvement in fatigue (110)(111)(112). Serotonin-norepinephrine reuptake inhibitors, selective serotonin reuptake inhibitors, or tricyclic antidepressants could improve the symptoms of fatigue (97). Hypovitaminosis D-associated fatigue should be managed with vitamin D supplements (113).…”
Section: Reviewmentioning
confidence: 99%
“…This approach should be continued until symptom improvement is achieved. The management includes non-pharmacological and pharmacological modalities (97). Non-pharmacological modalities always begin with patient education.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation